Review of the European standard for postgraduate training of medical specialists in internal medicine and prospects for implementation in Russian Federation - Z. D. Kobalava; S. A. Rachina; E. E. Shkolnikova (Izdatelstvo OKI, 2020)
Relevance. Residency remains an integral part of quality postgraduate education in Russia. Improving the education system of medical workers and creating a system of motivation for their quality work is one of the priority tasks implemented within the framework of the Concept of development of the healthcare system in the Russian Federation until 2020.Objective. Comparison of the European standard of postgraduate training of medical specialists in the field of "internal diseases" with the existing training system in the Russian Federation.Results. The residency program of the Russian Federation pursues a similar aim to the European standard - the training of a qualified general practitioner. The program is based on a modular system and includes the study of various disciplines, an extensive practice program and state final certification. An analysis of the content of the work programs of the disciplines indicates that the training is aimed at the formation of both universal (general cultural) competencies, which are essentially similar to CanMEDS, and professional competencies. There is no significant difference between the list of knowledge, skills and practical skills that a general practitioner must possess after graduation from residency in Europe and Russian Federation. However, the development of a similar program in the Russian Federation takes much less time (2 years or 4,320 hours), which raises a logical question about the quality of training.Conclusion. Despite the diff erence in the programs for postgraduate training of internist (primarily in terms of hours), the learning goal is the formation of similar competencies. It should also be noted a well-structured control system, which makes it possible to objectively evaluate the acquired competencies and adjust the individual learning process.